Validation of the Thermo Scientific™ SureTect™Staphylococcus aureus PCR Assay for the Detection of Staphylococcus aureus in Dairy Matrixes: AOAC Performance Tested MethodSM 052101. (6th October 2021) - Evans, Katharine; Faulds, Nikki; Crabtree, David; Hughes, Annette; Sohier, Daniele; Manthe, Craig; Hahs, Matthew; Heikkinen, Pauliina; Hurskainen, Emmi; Koch, Kateland; Thompson, Wesley; Bastin, Benjamin; et al.
Abstract: Background: The Thermo Scientific ™ SureTect ™ Staphylococcus aureus PCR Assay is a real-time PCR assay for the detection of Staphylococcus aureus in dairy samples. Objective: The Thermo Scientific SureTect Staphylococcus aureus PCR Assay was evaluated for AOAC Performance Tested Method SM certification. Methods: Inclusivity/exclusivity, matrix studies, product consistency and stability, and robustness testing were conducted to assess the method's performance. For the matrix study, the method was validated on the Applied Biosystems ™ QuantStudio ™ 5 Real-Time PCR instrument and the Applied Biosystems 7500 Fast Real-Time PCR instrument against the ISO 6888-3:2003 Microbiology of food and animal feeding stuffs—Horizontal method for the enumeration of coagulase-positive staphylococci ( Staphylococcus aureus and other species)—Part 3: Detection and MPN technique for low numbers, and the U.S. Food and Drug Administration (FDA) Bacteriological Analytical Manual (BAM) Ch. 12, Staphylococcus aureus, 2016, reference methods. Results: Matrix studies showed no statistically significant differences between the candidate and reference methods or between presumptive and confirmed results. The inclusivity/exclusivity study correctly identified/excluded all strains analyzed. Robustness testing showed no statistically significant difference in assay performance after set method parameter deviations, and product consistency and stability studies demonstrated no statistically significant differences in performance between kit lots at different expiration points. Conclusion: The data presented show that the assay is a rapid and reliable workflow for the detection of S. aureus from dairy matrixes. Highlights: The PCR assay allows for fast, reliable detection of S. aureus in dairy matrixes with results obtained in as little as 80 min post enrichment.